If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 7 = 0 Reorder the terms: 7 + 6x = 0 Solving 7 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 6x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 6x = 0 + -7 6x = 0 + -7 Combine like terms: 0 + -7 = -7 6x = -7 Divide each side by '6'. x = -1.166666667 Simplifying x = -1.166666667
| 10x-6-x-3= | | 0.2x-0.6x-27=1 | | 4x+30=14x-80 | | x-2=-9 | | 10-15x+2=10x+5-11x | | ln(x+3)=0 | | -4x^2+5x+6=0 | | 4x+53=7x+8 | | 29=5x+21+3x | | x+(x+1)+(x+2)=90 | | 15=2h+5 | | 9x^2-6x-24=0 | | 6x+8x+10x=120 | | 2x+8-9x=7+2x-2 | | 5r^2=40 | | 1=0.2x-0.9x-55 | | 2X+5t=1500 | | -7(4x-5y+6)= | | 4y+9-7=-6 | | 2x+5x=1500 | | 5xy= | | sx^2-98=0 | | 9x+x=9x-2 | | (x+6)*2=18 | | 7x+2x=2x+1+6x | | .375w-22=-1.125w+4 | | 12=9x-2 | | 12x^2=25x-12 | | x*5=15 | | 4x^2-5x=-1 | | 9x+8=7x+-4 | | 8x-9y=11 |